Size Optimized Load Independent Constant Current and Constant Voltage Wireless Charging System for EVs - Gautam, Kirshan Kumar; Chatterjee, Amitabh; Santra, Subhendu Bikash; Prasad, Dinkar (IEEE journal of emerging and selected topics in industrial electronics (Print), 2025)
Efficient and compact wireless charging system (WCS) for Electric Vehicles (EVs) requires a constant current-constant voltage (CC-CV) output which ensures the safety and longer life span of Li-ion batteries. In this article a simple, size-optimized WCS is designed using a series-series compensation topology to achieve load independent CC-CV output. The seamless transition from CC to CV mode is achieved by changing the switching frequency assisted by a simple analog switch (DG 201). Transmission line parameter based simplified technique is proposed to derive switching frequencies for CC-CV output. Furthermore, from the load independent voltage and current gain using frequency-domain analysis, switching frequencies for CC-CV mode is verified. In addition, all inverter switches are designed to operate with zero voltage switching (ZVS) at turn-ON and zero current switching (ZCS) at turn-OFF during CC charging and ZVS at turn ON during CV charging. To improve power density a kVA/kW optimization technique is employed which minimizes the size of reactive components. An optimized kVA/kW ratio of 19.95 is achieved at Q = 4 .47 for a coupling coefficient 0.2. A 600 W prototype has been designed and developed to validate the proposed WCS. It operates at 115.6 kHz in CC mode and 129 kHz in CV mode with a coupling coefficient of 0.2 and achieves a peak efficiency of 92%.